Mas vale morir de pie luchando que de rodillas mendigando - Figueroa, Lorena; Guevara, Renato; Alarcon, Rosy; Mogollon, Natalia (Pontificia Universidad Católica del Perú, 2018)
The following work aims to understand why the retirees of the Central Nacional de Jubilados y Pensionistas del Perú (CENAJUPE) organize politically. There is a wide literature that has placed older adults as passive subjects. However, this organization demonstrates an atypical and particular case in the Peruvian context. The findings show us that the main motive for their organization is what we have called a “Politicized Waiting”. In other words, retirees actively wait for their pensions to rise, which can be reflected in their marches, sit-ins, complaints, etc. Thus, this wait is sustained due to the existence of two gestures: the small achievements they have obtained and the hopes in the new leaders. In addition, there are two other factors that contribute to the organization lasting: on the one hand, resources that enable and/or limit its organization (union experience, connection with other organizations, family support), and, on the other, non-political reasons (the “being active” of retirees and the support network) that help retirees continue to participate actively despite not having yet achieved their main objective: raising their pensions.

El siguiente trabajo busca entender por qué los jubilados de la Central Nacional de Jubilados y Pensionistas del Perú (CENAJUPE) se organizan políticamente. Existe un amplia literatura que ha situado a los adultos mayores como sujetos pasivos, sin embargo, esta organización demuestra un caso atípico y particular en el contexto peruano. Los hallazgos nos muestran que el principal motivo para su organización es lo que hemos denominado una “Espera Politizada”; es decir, los jubilados esperan por el alza de sus pensiones de manera activa, lo que se puede reflejar en sus marchas, plantones, denuncias, etc. Así, esta espera se sostiene debido a la existencia de dos gestos: los pequeños logros que han obtenido y las esperanzas en los nuevos dirigentes. Además, existen dos factores adicionales que contribuyen a que la organización perdure: por un lado, recursos que posibilitan y/o limitan su organización (experiencia sindical, conexión con otras organizaciones, apoyo familiar), y, por el otro, motivos no políticos (el “ser activo” de los jubilados y la red de soporte) que contribuyen a que los jubilados sigan participando activamente a pesar de no haber conseguido aún su objetivo principal: el alza de sus pensiones.
Better to die on your feet fighting than on your knees begging
Keywords: Jubilados; Organización política; Espera politizada; Movilización de recursos; Motivos no políticos; https://purl.org/pe-repo/ocde/ford#5.04.01